A Comparison of Learning the Speech Acts of Requesting and Apologizing among EFL Learners through Input Enhancement and Input Flooding Approaches: Computer-Mediated Method versus Traditional Method - Bakhshi Jahromi, Iman; Ahmadi Shirazi, Masoumeh; Khomijani Farahani, Ali Akbar (Assessment and Practice in Educational Sciences, 2026)
The present study investigated the effects of input enhancement and input flooding on the learning of the speech acts of apologizing and requesting by learners of English as a foreign language (EFL). A total of 120 intermediate-level male and female learners were randomly selected and assigned to four groups of 30 participants each (computer-mediated input enhancement, computer-mediated input flooding, traditional input enhancement, and traditional input flooding), who received instruction over a specified instructional period. The instructional method, taking learners’ gender into account, was divided into two modes: computer-mediated and traditional. A pragmatics-based discourse completion test was used to collect the data. Independent-samples t-tests and one-way analysis of variance (ANOVA) were employed for data analysis. The findings indicated that the highest mean score for pragmatic knowledge belonged to the computer-mediated input flooding group (17.67), while the lowest mean score was observed in the traditional input enhancement group (12.90). No statistically significant differences were found between the other two groups. Overall, the results demonstrated that: (1) the computer-mediated method was more effective than the traditional method in promoting learners’ acquisition of speech acts; (2) the input flooding approach was more effective than the input enhancement approach in facilitating the learning of speech acts; (3) gender had no significant effect on the learning of speech acts among male and female learners; and (4) the group receiving computer-mediated input flooding instruction showed the greatest improvement in learning the speech acts of apologizing and requesting. These findings can be useful for selecting appropriate instructional methods and for improving EFL learners’ pragmatic knowledge in performing speech acts.